PENGARUH CORPORATE SOCIAL RESPONSIBILTY (CSR) TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2009-2013) - Ramadhana, Yusri; Afri Yuyetta, Etna Nur (Diponegoro Journal of Accounting, 2015)
This study aims to determine how the effect of the practice of Corporate Social Responsibility (CSR) by companies to the corporate performance, specifically corporate financial performance (accounting-based view) and corporate market performance (market-based view). In this study, the independent variable CSR that consists of six categories of CSR according to Global Reporting Initiative (GRI) namely economical impact, employment, environtment, product responsibilty, Social-Human Rights, and local people and based on Clarkson stakeholder framework will be tested its effect on the dependent variable corporate’s financial performance which is proxied by Return on Assets (ROA), Return On Equity (ROE), and Return On Sales (ROS) and corporate 's market performance which is proxied by Tobin's q. This study also used control variables, namely firm size, sales growth, and leverage. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) period in 2009-2013 with the total sample were 617 companies which determined by purposive sampling method. Data analysis in this research carried out by using the classical assumption, whereas hypothesis testing carried out by using multiple linear regression analysis with two-equation model. The results of this study show that CSR has positive and significant effect on the corporate's financial performance and corporate’s market performance. This study also found that the corporate's size has positive and signifikant effect on corporate’s market performance; leverage has negative and significant effect on the corporate's financial performance, and has positive and signifikant effect on corporate’s market performance; the corporate's sales growth has positive and significant effect on corporate’s financial performance and corporate’s market performance.